Morphometry, hematology, and plasma chemistry of common coot (Fulica atra) in Punjab, Pakistan. (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: The common coot (Fulica atra) is a medium-sized migratory bird wintering at different wetlands in Pakistan. It belongs to the order Gruiformes and family Rallidae. This study aimed to investigate the morphometry, hematology, and blood chemistry of common coots during the winter visit of 2022–2023. Materials and Methods: Thirty-two adult common coots were captured with the help of hunters holding valid licenses from six wetlands in Punjab, Pakistan. Each individual was sexed and subjected to different morphological measurements. Eighteen blood samples (3–5 ml) were collected from the basilic veins of adults for hematology and blood chemistry. Results: Results revealed that body weight ranged from 378 to 680 gm, with males significantly heavier than females. Length was not significantly different. Males showed dominance in most of the morphometric characteristics compared to females. Regarding hematological parameters and plasma chemistry, there was a sufficient difference between the genders in most of the studied parameters. Conclusion: The male coot was significantly larger compared to the female, except for total length. Hematology and plasma chemistry showed significant differences between genders.J. Adv. Vet. Anim. Res., 12(1): 312–320, March 2025http://doi.org/10.5455/javar.2025.l898